Pengaruh Persepsi Kemudahan dan Keamanan Penggunaan QRIS Terhadap Minat Transaksi Digital pada Generasi Z di Kecamatan Cikarang Barat, Kabupaten Bekasi - Putri Rizki Windiarti; Nurul Hidayah (LP3M Universitas Putra Bangsa, 2026)
This study examines the effects of perceived ease of use and perceived security of QRIS on digital transaction intention among Generation Z in West Cikarang District, Bekasi Regency. A quantitative research approach was employed using questionnaires distributed to 100 respondents selected through purposive sampling. The collected data were analyzed using multiple linear regression with the assistance of SPSS. The results demonstrate that perceived ease of use has a positive and significant effect on digital transaction intention (t = 8.291, p < 0.001), indicating that users are more likely to adopt QRIS when they perceive the system as simple and convenient to use. Perceived security also has a positive and significant effect on digital transaction intention (t = 4.148, p < 0.001), suggesting that users' confidence in transaction safety and data protection encourages the adoption of digital payment services. Furthermore, perceived ease of use and perceived security simultaneously exert a significant influence on digital transaction intention (F = 116.653, p < 0.001). The coefficient of determination (R² = 0.706) indicates that 70.6% of the variation in digital transaction intention is explained by these two variables. These findings highlight that ease of use and system security are key determinants of Generation Z's intention to adopt QRIS as a digital payment method.